EVALUATION OF DIGITAL MARKETING PERFORMANCE IN ELECTRONIC GOODS INDUSTRY: AN EMPIRICAL STUDY - Saravanan Rangaswamy (Institute for Research and European Studies, 2021)
The last two decades have witnessed a skyrocketing growth in digital marketing that made customers interested in purchasing products particularly electronic goods. However, it is not known whether those customers attained satisfaction through this purchase. To confirm the fact, this research has attempted to analyze the retention rate of digital marketing customers who have experience in purchasing electronic goods and for this purpose, 603 consumers of Tamilnadu (India) who have the purchase experience on a digital marketing basis were selected on a simple random basis. Tools like structural equation modeling, percentage analysis, one-way ANOVA, and paired sample ‘t’ test were applied and the result revealed that only customer satisfaction has mediated the influence of digital marketing on their loyalty but, the important parameter, trust has a negative role between these constructs. Marketers need to create trust about the product with the actual features as informed in digital marketing so that consumers can reach a high level of satisfaction and this may lead to a positive word of mouth. In addition, this enhances sales and enables marketers to attain profit maximization along with building consumer confidence.